Trade and foreign direct investment: Impact on economic growth and emissions in gulf cooperation council countries / Ahmed Saddam Abdulsahib Albu-Shabeeb - Albu-Shabeeb, Ahmed Saddam Abdulsahib (2014)

(untitled)
This study addresses foreign trade, FDI and carbon dioxide emission issues of the Gulf Cooperation Council states (GCC), namely the United Arab Emirates, Bahrain, Saudi Arabia, Oman, Qatar and Kuwait. We have found that the intra-regional trade remains modest, as the trade intensity index showed negative signs except in the UAE, and Saudi Arabia. The study used a gravity model and confirms that the size of real GDP has a significant impact in determining the foreign trade. Moreover, the variable of transportation cost rate is not a concern for Saudi's foreign trade despite the increase, as Saudi Arabia as a hub economy tends to trade with countries like Australia and the UK more than with its nearby countries. The real GDP variable is the key agent that determines the level of foreign trade of GCC countries. The study concludes that the unified economic policy of the GCC countries has not achieved its target in terms of increasing the level of non-oil industries. Furthermore, transportation cost rate variable is not an important factor influencing trade of GCC countries. Besides, the study measured the impact of foreign trade and FDI on GCC economies. We found that the role of FDI is positive in UAE and negative in Saudi Arabia, while having no effect on the rest of the GCC countries. In addition, the study infers the continued importance of oil exports of all GCC members. The non-oil variable did not affect real GDP, except for the UAE, and the commodity imports have a positive impact except for Bahrain and the UAE. However, Gulf Cooperation Council countries are among the top 25 countries in terms of their contribution to increasing the level of carbon dioxide emissions and are much higher than the average for the world. Moreover, these countries emit from 45 per cent to 50 per iii cent of the total emissions of Arab countries, due to the significant role of extractive sectors as major sources of income to these economies. Therefore, the most important factors pertaining to the increasing carbon dioxide emissions in GCC countries over the period 1998-2008 were examined. In this respect, the study objective is to determine how much the FDI inflows, economic growth, and commodity imports influenced the increasing level of emissions during the period of study, and find which variable has most effect. For this purpose, an empirical model was estimated in order to obtain the impact of said variables on GCC countries. The model of carbon dioxide emissions as a function of FDI inflows, real GDP, commodity imports and health expenditure was examined using a panel data technique. We found that the real GDP has had an important positive effect on increasing carbon dioxide emissions in all GCC countries during the period 1998-2008, where it is the main cause of air pollution in these countries, while FDI inflows indicates its positive effect only in Qatar. Finally, the health expenditure variable has impacted reducing the level of emissions in Oman and Kuwait, similarly to the commodity import variable in Saudi Arabia.